iWrite System Blended Teaching: A Meta-Analysis of its Impact on College Students' English Writing Ability - Xu , Xiaofei; Baharum, Harmi Izzuan Bin (Journal of Ecohumanism, 2024)
With the rapid development of educational technology, intelligent writing assistance systems are increasingly used in higher education. However, there is a lack of comprehensive empirical evidence on its actual effects. This study aims to systematically evaluate the impact of iWrite system on college students' English writing ability under the blended teaching model through meta-analysis . A comprehensive analysis was conducted on 42 relevant empirical studies published from 2010 to 2023, with samples from 1876 college students in five countries. The study adopted a random effects model and found that the iWrite blended teaching system had a significant positive impact on students' overall writing ability (d = 0.68, 95% CI [0.52, 0.84]). Further analysis of the moderating effects showed that implementation period (β=0.04, p<0.01), teacher training intensity (β=0.15, p<0.001), and students’ initial English proficiency (β=-0.09, p<0.05) were significant affected the effectiveness of the intervention. This study not only provides strong evidence for the effectiveness of the iWrite system in college English writing teaching, but also provides important inspiration for optimizing blended teaching practices. The research results have important theoretical and practical significance for colleges and universities to formulate writing teaching policies, improve curriculum design, and improve teaching effects.